Pemanfaatan Data ARR (Automatic Rainfall Recorder) Untuk Peningkatan Efektifitas Model Hujan Satelit (Studi Kasus DAS Indragiri) - Hendra, Yuli; Fauzi, Manyuk; Sutikno, Sigit (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The availability of data on hydrological modeling always become a problem considering the incompleteness and the imprecision of data. As the development of technology, many models of hidrology using data acquired from the satellite have emerged. The accuracy and the model correlation was still unachieved from the previous research using satellite data. This problems was caused by the unstable weather conditions thus the process of recording and dowloading of the satellite data become less optimum. hence this research conducts the modeling of rainfall-runoff to improve the effectivity of satellite rainfall model by using the ground rainfall data, such as satellite rainfall data modification to improve the accuracy and the correlation of the model using IFAS program in Indragiri Watershed, Riau Province. The research conducted simulation, calibration for 2004 and verification for 2006. The result of the research showed that upon satellite rainfall modification for 2004 an increase in the effectiviness of the satellite rainfall model with increased accuracy and correlation on hydrological modeling with coefficient of correlation (R) value 0,811, volume error (VE) 0,099%, and coefficient of efficiency (CE) 0,520.Keywords: rainfall-runoff modeling, satellite rainfall, ground rainfall, satellite rainfall modification, IFAS.